Phase Mapping Using a Combination of Multi-Functional Scanning Electron Microscopy Detectors and Imaging Modes - Gang Liu; Yonghua Zhao; Shuai Wang (Metals, 2024)
Microstructure degradation and phase transformations are critical concerns in nickel-based superalloys during thermal exposure. Understanding the phase transformation mechanism requires the detailed mapping of the distribution of each phase at different degradation stages and in various precipitation sizes. However, differentiating between phases in large areas, typically on the scale of millimeters and often relying on scanning electron microscopy (SEM) techniques, has traditionally been a challenging task. In this study, we present a novel and efficient phase mapping method that leverages multiple imaging detectors and modes in SEM. This approach allows for the relatively rapid and explicit differentiation and mapping of the distribution of various phases, including MC, M23C6, γ′, and η phases, as demonstrated in a typical superalloy subjected to aging experiments at 800 °C.